A review of the genus Kanakia Distant, 1892 (Insecta: Hemiptera, Cicadoidea, Cicadidae) from New Caledonia - Delorme, Quentin; Mille, Christian; Jourdan, Hervé (Zootaxa, 2016)
Among New Caledonian cicada taxa, the endemic genus Kanakia Distant, 1892 appears as the most spectacular one, especially because of the large size of its species (length up to 50 mm for males). Recent new specimen collections helped to clarify the taxonomy of this spectacular genus. According to morphological characteristics, we were able to redefine and to split the present genus into three distinct genera: Kanakia Distant, 1892, Pseudokanakia Delorme gen. nov. and Panialna Delorme gen. nov. These two new genera are monotypic and have been respectively established from revision of Kanakia flavoannulata (Distant 1920) and Kanakia parva Boulard 1991. Also, the type species, Kanakia typica Distant, 1892, appears to be a complex of cryptic species. New acoustic and morphological observations allowed us to redefine K. typica and to describe four new species in this complex: Kanakia paniensis Delorme sp. nov., Kanakia rana Delorme sp. nov., Kanakia salesnii Delorme sp. nov. and Kanakia fuscocosta Delorme sp. nov. Kanakia gigas Boulard 1988 is also briefly discussed and the female is described. An identification key of the Kanakia species and allied genera is also provided.